P05.85 Mismatch repair system and immune-checkpoints profile in brain metastasis: study of 65 patients. (19th September 2018) - Patanè, M; Calatozzolo, C; Farinotti, M; Cacciatore, F C; Silvani, A; Anghileri, E; DiMeco, F; Pollo, B
Abstract: Background: Brain metastases (bMTS) represent the most common intracranial tumors occurring in 10–20% of patients with cancer. Despite several therapeutic approaches, patients continue to face a dismal prognosis. Immunotherapies could represent a promising challenge to improve the prognosis. Immune checkpoints (PD-L1/PD-1, CTLA-4/CD80 and CD28) are negative regulators of T-cells and the inhibition of this pathway could activate the intrinsic immune response against tumor. FDA has recently approved Pembrolizumab, a PD-1 inhibitor, for metastatic solid tumors displaying mismatch-repair system (MMR) deficiency. The MMR system allows the repair of DNA mismatches during replication and consists of two heterodimers: MSH6/MSH2 and PMS2/MLH1. Mutations in MMR genes are associated to higher risk of developing cancers, but the high rate of acquired somatic mutations generates the exposure of neoantigens activating immune response. Material and Methods: To investigate the occurrence and the role of MMR deficiency in bMTS, we have performed an immunohistochemical analysis (IHC) on 65 bMTS from lung, breast, colon, kidney cancers and melanomas to evaluate the expression of MMR proteins (MSH6, MSH2, PMS2, MLH1) and immune checkpoints (PD-L1, CTLA-4 and CD28). We have also characterized infiltrating lymphocytes and myeloid cells by IHC for CD3, CD4, CD8, CD20, CD68, CD163 and Iba1 expression. All results obtained have been related to clinical data. Results: We have found a loss of expression of MMR proteins (mostly PMS2 and MLH1) in 40% of patients, significantly related to a worst prognosis. The 20% of cases showed overexpression of PD-L1 on tumor cells, while CTLA-4 and CD28 were mainly expressed in infiltrating lymphocytes. The expression of these markers was mainly related to MMR protein loss, especially in bMTS derived from lung cancer. Many bMTS showed high presence of infiltrating lymphocytes and microglia, both in the tumor mass and surrounding parenchyma, not strictly related to MMR loss expression, but linked to a good prognosis. Conclusion: In our study we proposed that it is possible to define the MMR status and the immunological profile of bMTS with an IHC analysis, and this study confirmed that MMR evaluation by IHC could be also used to assess quickly microsatellites instability in bMTS avoiding further expensive analysis. This method could provide an early prognostic panel useful for the clinicians, and these data may suggest which patients could be good candidates for immunotherapy.